Acquisitions and Partnerships of Reliance New Energy Limited (RNEL) - Reliance Industries Limited (2022)
RIL, through its subsidiary company Reliance New Energy Ltd (RNEL), announces acquisitions and partnerships to develop the New Energy ecosystem. • USD 144 million investment in energy storage company Ambri Inc along with strategic investors Paulson & Co. Inc. and Bill Gates, and a few others, as part of Reliance’s long-duration energy storage systems business globally • USD 771 million acquisition of REC Solar Holdings AS (REC Group), one of the world’s leading solar cells/panels and polysilicon manufacturing companies • 40% stake acquisition in Sterling & Wilson Solar, one of the largest EPC and O&M providers globally, to provide turnkey solutions in the New Energy value chain • USD 29 million (EUR 25 million) investment in Germany’s NexWafe and a partnership for the joint technology development and commercialization of high-efficiency monocrystalline “green solar wafers” • Collaboration with Denmark’s Stiesdal A/S on development and manufacturing of their HydroGen Electrolyzers in India, which will produce hydrogen at a significantly lower cost compared to current levels, thus paving the way for rapid decarbonization and commercialization of affordable Green Hydrogen • GBP 100 million acquisition of leading global sodium-ion battery technology company Faradion Ltd, and an additional GBP 25 million investment as growth capital to accelerate commercial roll out.